PEMETAAN SOSIAL BUDAYA PADA MASA KULIAH KERJA NYATA INTEGRATIF DI DESA SAKERTA BARAT KECAMATAN DARMA KABUPATEN KUNINGAN - Ganjar Mawardi Fitriadi; Frendy Rahmansyah (BHAKTI: JURNAL PENGABDIAN DAN PEMBERDAYAAN MASYARAKAT, 2022)
This activity aims to carry out socio-cultural mapping as the first step for Integrative KKN in West Sakerta Village, Darma District, Kuningan Regency. The focus is on the fields of economy, health, education, religion, and community culture. The method used in this activity is PRA in the form of (a) building communication with several community nodes, (b) conducting historical tracing as a cultural foothold, (c) conducting FGDs (Focus Group Discussions) with social units and stakeholders, ( d) critical reflection on the findings which are confirmed to policy makers and stakeholders. The results of the activity include, from the economic field, it has the potential to be developed in the agricultural industry, for example, cassava chips. The field of education has received less attention considering the low interest in studying because people's needs are still in the economic sector. The health sector is not good with indicators of the absence of a good waste disposal system and the poor infrastructure of the Puskesmas. The field of religion is not good considering that religious education is only obtained in religious education in schools. In the cultural field, it was found that Sakerta's original culture was undermined, such as Wayang, Reog, Jaipong, and Qasidahan